Minimally Invasive Surgery in Modern Medicine: A Review of Laparoscopic Techniques, Indications, and Postoperative Outcomes - Czarnota, Maksymilian; Adamowicz, Martyna; Górniak, Aleksandra (Journal of Education, Health and Sport, 2025)
Background: Minimally invasive surgery has reshaped operative care, yet contemporary evidence is fragmented across specialties. Objective: To integrate recent data on laparoscopic indications, technological advances and patient-centred outcomes. Methods: Narrative review of 37 PubMed-indexed studies (2022–2025) encompassing randomised trials, cohort studies and meta-analyses in general, hepatobiliary, bariatric, gynaecologic and urologic surgery. Extracted variables included operative time, blood loss, complications, length of stay, quality-of-life and long-term results. Results: Relative to open surgery, laparoscopy reduced blood loss by 30–60 %, wound infections by up to 70 % and hospital stay by 1–3 days without prolonging operative time. Oncologic clearance and five-year survival were preserved in colorectal, gastric and cervical cancers. Enhanced visualisation, single-incision access and staple-line optimisation improved technical efficiency, while restrictive fluid and ERAS pathways halved pulmonary complications and hastened recovery. Elderly and frail patients experienced lower pulmonary morbidity and faster functional return, while paediatric and fertility-preserving gynaecologic procedures maintained safety and sustained quality of life. Conclusions: Laparoscopic techniques should be preferred whenever technically feasible, including complex, emergency and high-risk scenarios, provided adequate expertise and structured peri-operative care. Priority research areas include harmonised outcome definitions, registries with ≥ 10-year follow-up, robust cost-utility analyses and trials in under-represented populations to consolidate the value and equity of modern minimally invasive surgery.